Phyllanthus carmenluciae, a supreme species of Phyllanthus (Phyllantaceae) from Brazil - Ribeiro, Rayane De Tasso Moreira; Neto, Raimundo Luciano Soares; Loiola, Maria Iracema Bezerra (Phytotaxa, 2017)
We describe a new species of Phyllanthus, currently known only from the Serra de Baturité mountains in Ceará State, Brazil, a region of predominantly dense ombrophilous forests. Phyllanthus carmenluciae is quite distinct from other species of the genus, and is therefore considered supreme, and is also named to honor the current president of the Brazilian Federal Supreme Court (STF), Cármen Lúcia Antunes Rocha. This species is characterized by having pubescent cylindrical branches, a mucronate leaf apex, inflorescences in bisexual cymules, with two proximal staminate flowers and two distal pistillate flowers, and anthers sagittate with vertical clefts. We present information concerning ecological aspects of the species, geographic distribution, affinities with other species of Phyllanthus, photographs, and its conservation status.